The Clinic for Assessment of Youth at Risk (CAYR): 10 years of service delivery and research targeting the prevention of psychosis in Montreal, Canada. Issue 2 (23rd November 2015) - Pruessner, Marita; Faridi, Kia; Shah, Jai; Rabinovitch, Mark; Iyer, Srividya; Abadi, Sherezad; Pawliuk, Nicole; Joober, Ridha; Malla, Ashok K.
Abstract: Aim: In the context of an increasing focus on indicated prevention of psychotic disorders, we describe the operation of the Clinic for Assessment of Youth at Risk (CAYR) over 10 years, a specialized service for identification, monitoring and treatment of young individuals who meet ultra‐high risk (UHR) criteria for psychosis, and its integration within the Prevention and Early Intervention Program for Psychosis (PEPP) in Montreal, Canada. Methods: We outline rationale, development, inclusion and exclusion criteria, assessment, services offered, community outreach and liaison with potential referral sites, and our research focus on risk and protective factors related to the neural diathesis–stress model of psychosis. Results: Between January 2005 and December 2014, CAYR has received 370 referrals and accepted 177 patients who met UHR criteria based on the Comprehensive Assessment for At Risk Mental States. Conversion rates to a first episode of psychosis were 11%. Our research findings point to high subjective stress levels, poor self‐esteem, social support and coping skills, and a dysregulation of the hypothalamus–pituitary–adrenal axis during the high‐risk phase. Conclusions: Our efforts at community outreach have resulted in increasing numbers of referrals and patients accepted to CAYR, highlighting the relevance of and need for a high‐risk programme in the Montreal area. Patients with psychotic symptoms can be immediately assigned to the first‐episode psychosis clinic within PEPP, which has likely contributed to the low conversion rates observed in the UHR group. Our research findings on stress and protective factors emphasize the importance of psychosocial interventions for high‐risk patients.